(untitled) (International Educators Conference, 2025)
This study explores the influence of cultural values and norms on the pragmatic use of language in English-speaking countries. Pragmatics—the study of language in context—encompasses how speakers use indirectness, politeness strategies, speech acts, and conversational implicature to convey meaning beyond literal words. Despite sharing a common language, English-speaking countries such as the United States, the United Kingdom, Canada, and Australia exhibit significant variation in pragmatic conventions due to differing historical, social, and cultural backgrounds. Through a comparative analysis of conversational data, media discourse, and cross-cultural studies, the research identifies how cultural dimensions—such as individualism vs. collectivism, power distance, and attitudes toward formality—influence expressions of politeness, disagreement, humor, and requests.